B76 - La Biennale di Venezia 1976 : Section of Visual Arts and Architecture - General Catalogue : Environment, Participation, Cultural Structures : First volume & Second volume. - La Biennale di Venezia, 1976 (Venezia : Alfieri, edizioni d'arte, 1976)
Maeyer, Marcel ; Stroobant, Dominique ; Tas, Filip Josef ; Willaert, Joseph ; Lavier, Bertrand ; Raynaud, Jean-Pierre ; Beuys, Joseph ; Gerz, Jochen ; Ruthenbeck, Reiner ; Long, Richard ; Karavan, Dani ; Motherwell, Robert ; Ryman, Robert ; Martin, Agnes ; Irwin, Robert ; Tuttle, Richard ; etc.
Second volume: La Biennale di Venezia 1976 : Section of Visual Arts and Architecture - General Catalogue : Environment, Participation, Cultural Structures : The "Werkbund" 1907, the Origins of Design ; Rationalism and Architecture in Italy during the Fascist Regime ; Europe-America Historical Centre - Suburbia ; Design / Ettore Sottsass an Italian Designer ; Design / Five Graphic Designers ; Design / The Forms of Glass ; Man Ray Testimony through Photography ; International Events '72-76
La Biennale di Venezia, 14.07 - 10.10.1976
Engels
kunstcatalogus